Diagnosis of an intermediate case of maple syrup urine disease: a case report - Lin, Yun-Ting; Cai, Yan-Na; Ting, Tzer Hwu; Liu, Li; Zeng, Chun-Hua; Su, Ling; Peng, Min-Zhi; Li, Xiu-Zhen (Baishideng Publishing Group, 2023)
BACKGROUND: Maple syrup urine disease (MSUD) is an autosomal recessive genetic disorder caused by defects in the catabolism of the branched-chain amino acids (BCAAs). However, the clinical and metabolic screening is limited in identifying all MSUD patients, especially those patients with mild phenotypes or are asymptomatic. This study aims to share the diagnostic experience of an intermediate MSUD case who was missed by metabolic profiling but identified by genetic analysis. CASE SUMMARY: This study reports the diagnostic process of a boy with intermediate MSUD. The proband presented with psychomotor retardation and cerebral lesions on magnetic resonance imaging scans at 8 mo of age. Preliminary clinical and metabolic profiling did not support a specific disease. However, whole exome sequencing and subsequent Sanger sequencing at 1 year and 7 mo of age identified bi-allelic pathogenic variants of the BCKDHB gene, confirming the proband as having MSUD with non-classic mild phenotypes. His clinical and laboratory data were retrospectively analyzed. According to his disease course, he was classified into an intermediate form of MSUD. His management was then changed to BCAAs restriction and metabolic monitoring conforming to MSUD. In addition, genetic counseling and prenatal diagnosis were provided to his parents. CONCLUSION: Our work provides diagnostic experience of an intermediate MSUD case, suggesting that a genetic analysis is important for ambiguous cases, and alerts clinicians to avoid missing patients with non-classic mild phenotypes of MSUD.